Rancang Bangun Aplikasi Pengelolaan Aduan Perbaikan Jalan Manokwari Berbasis Website: Design Of a Website-Based Manokwari Road Repaid Complaint Management Application - Marcelin Febriyani; Cristian Dwi Suhendra; Lion Ferdiand Marini (JISTECH: Journal of Information Science and Technology, 2025)
Manokwari City as the capital of West Papua Province has a fairly extensive road network. However, it is not uncommon to find road damage that can disrupt community activities. Currently, Manokwari people who want to report road damage often do not know the right place or platform to report the problem. This causes not all reports of road damage to be detected and handled quickly. This research uses the waterfall method, which consists of the stages of needs analysis, system design, implementation, and testing. Applications built using the PHP programming language and the Laravel framework, as well as MySQL as a database can be used to help the admin in facilitating the process of collecting damaged road complaint data in Manokwari. The data inputted is damaged road data (starting from the title of the complaint report, the contents of the complaint report, the name of the village, the name of the road, the name of the reporter, the reporter's number and uploading photos of the damaged road) from those reported by the community. Furthermore, the application displays automatically in each process carried out starting from the admin seeing where the damage is (village name and street name), the contents of the damage report after which it is dispatched to the agency responsible for carrying out the repair. The result of making this solution is a computerized application in entering data on the results of public complaints that report roads and make it easier for admins to input and find out damaged roads in the application.